PEREMPUAN MENJADI IMAM SHALAT (Kajian Hukum dalam Perspektif Hadis) - Maidin, M. Nasir (AL-MAIYYAH, 2016)
This paper examines the hadith related to the allowance of woman to be the priest in prayer where few men are her makmum. The scholars have different opinions about it; some scholars allowed, but other didnât. Based on the writerâs analysis, the hadith which allowed woman to be the priest in prayer where few men are her makmum is categorized hadith daif. Hadith daif for the majority of scholarsâ view cannot be used as hujjah in Islamic law.